New fixed point results for Ciric twisted contraction with applications to market models - Khayyam Shah, Syed; Sarwar, Muhammad; Abodayeh, Kamalidin; Chasreechai, Saowaluck; Sitthiwirattham, Thanin (Fixed point theory and algorithms for sciences and engineering, 2025)
This manuscript aims to develop the concept of almost Ciric twisted ( ∝ , μ ) Θ-contraction and prove novel fixed point results. In this direction, several ideas and definitions from the literature have been re-evaluated. Utilising the idea of twisted ( ∝ , μ ) mappings and Θ-contraction, new results of almost ciric type are presented. The inclusion of examples supports the presented results. Finally, the results are employed to guarantee the existence and ensure the uniqueness of fractional differential equations associated with the stability of the production-consumption equilibrium and economic growth model.